2010
DOI: 10.1007/s12122-010-9081-6
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance and Health Care Demand Among the Self-employed

Abstract: Individual insurance, Group insurance, Instrumental variables, Medical expenditure panel survey, I11, J32, C31,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Health insurance is considered a potential benefit for health, which has led to a great deal of research by scholars on the subject. Numerous studies from a global perspective, in both developing and developed countries, have shown that health insurance can improve an individual's health status by increasing the utilization rate of health services [38][39][40].…”
Section: Possible Reasons For Gender Differences In the Health Level ...mentioning
confidence: 99%
“…Health insurance is considered a potential benefit for health, which has led to a great deal of research by scholars on the subject. Numerous studies from a global perspective, in both developing and developed countries, have shown that health insurance can improve an individual's health status by increasing the utilization rate of health services [38][39][40].…”
Section: Possible Reasons For Gender Differences In the Health Level ...mentioning
confidence: 99%
“…propose a simulation based full maximum likelihood method for single equation count data models (generalized to the case of multivariate counts by Fabbri and Monfardini, 2011). Zimmer (2010) adopts instead a two step procedure, following the suggestion of Terza et al (2008). This latter study stresses that in many non linear contexts replacing predicted endogenous variables in the second stage leads to inconsistent estimators, and points to 2SRI to obtain valid inference, including exogeneity tests.…”
Section: Introductionmentioning
confidence: 99%